(untitled) (Academicia Globe: Inderscience Research, 2023)
The need to research the theoretical foundations and priority areas of food safety in Uzbekistan based on the implementation of the food program determined the relevance of this research topic. Livestock and meat production - agriculture is one of the important branches of the network. It is a source of protein from livestock such as milk, meat, eggs, honey, fish, industrial production, raw materials for the processing industry (milk, meat, leather, wool, cocoons, etc.) and plants. serves by preparing organic fertilizers for plant breeding. As a result of economic reforms and structural changes and diversification carried out in this sector, the number of cattle in our republic increased from 6 million 571.8 thousand heads in 2005 to 12 million 414.7 thousand heads in 2017 or 188.9 percent, of which the number of cows increased from 2 million 821.3 thousand to 4 million 418.3 thousand or 156.6 percent, and the number of sheep and goats increased from 11 million 351.9 thousand to 20 million 680.5 thousand per head or 182.2 percent, and the number of poultry increased from 18 million 775.7 thousand to 71 million 343.4 thousand or 3.8 times.